Construction of cellulose-degrading microbial consortium and evaluation of their ability to degrade spent mushroom substrate - Long, Junqiao; Wang, Xueli; Qiu, Shuyi; Zhou, Wei; Zhou, Shaoqi; Shen, Kaiwei; Xie, Lili; Ma, Xiao; Zhang, Xuyi (Frontiers in Microbiology, 2024)
Introduction Spent mushroom substrate (SMS) is a solid waste in agricultural production that contains abundant lignocellulosic fibers. The indiscriminate disposal of SMS will lead to significant resource waste and pollution of the surrounding environment.The isolation and screening of microorganisms with high cellulase degradation capacity is the key to improving SMS utilization. Methods The cellulose-degrading microbial consortiums were constructed through antagonism and enzyme activity test. The effect of microbial consortiums on lignocellulose degradation was systematically evaluated by SMS liquid fermentation experiments. Results In this study, four strains of cellulose-degrading bacteria were screened, and F16, F, and F7 were identified as B. amyloliquefaciens, PX1 identified as B. velezensis. At the same time, two groups of cellulose efficient degrading microbial consortiums (PX1 + F7 and F16 + F) were successfully constructed. When SMS was used as the sole carbon source, their carboxymethyl cellulase (CMCase) activities were 225.16 and 156.63 U/mL, respectively, and the filter paper enzyme (FPase) activities were 1.91 and 1.64 U/mL, respectively. PX1 + F7 had the highest degradation rate of hemicellulose and lignin, reaching 52.96% and 52.13%, respectively, and the degradation rate of F16 + F was as high as 56.30%. Field emission scanning electron microscopy (FESEM) analysis showed that the surface microstructure of SMS changed significantly after microbial consortiums treatment, and the change of absorption peak in Fourier transform infrared spectroscopy (FTIR) and the increase of crystallinity in X-ray diffraction (XRD) confirmed that the microbial consortiums had an actual degradation effect on SMS. The results showed that PX1 + F7 and F16 + F could effectively secrete cellulase and degrade cellulose, which had practical significance for the degradation of SMS. Discussion In this study, the constructed PX1 + F7 and F16 + F strains can effectively secrete cellulase and degrade cellulose, which holds practical significance in the degradation of SMS. The results can provide technical support for treating high-cellulose solid waste and for the comprehensive utilization of biomass resources.